2020
DOI: 10.1007/s12298-020-00762-w
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of dioscorealide B production by elicitation in shoot cultures of Dioscorea membranacea Pierre ex Prain & Burkill

Abstract: Dioscorealide B is an important secondary metabolite isolated from Dioscorea membranacea Pierre ex Prain & Burkill. The effect on secondary metabolite content of different concentrations of two elicitors [jasmonic acid (JA) and salicylic acid (SA)], and of medium status and JA exposure period were investigated. In the JA and SA concentration experiment, 6-week-old shoots were cultured on MS medium supplemented with 8.87 lM BA (6-benzyladenine) in combination with 100-500 lM JA or 50-200 lM SA for 3 weeks. MS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…An increased accumulation of anti-inflammatory alkaloids (pteropodine, isopteropodine, speciophylline, rumberine, hameline and palmirine) was reported in JA elicited Hamelia patens ( Flores-Sanchez et al, 2016 ). The highest dioscorealide B (a phenolic compound) contentwas recorded in the 100 μM JA elicited in vitro shoots of Dioscorea membranacea ( Jirakiattikul et al, 2020 ).…”
Section: Elicitation Of Secondary Metabolites Using Jasmonatesmentioning
confidence: 99%
“…An increased accumulation of anti-inflammatory alkaloids (pteropodine, isopteropodine, speciophylline, rumberine, hameline and palmirine) was reported in JA elicited Hamelia patens ( Flores-Sanchez et al, 2016 ). The highest dioscorealide B (a phenolic compound) contentwas recorded in the 100 μM JA elicited in vitro shoots of Dioscorea membranacea ( Jirakiattikul et al, 2020 ).…”
Section: Elicitation Of Secondary Metabolites Using Jasmonatesmentioning
confidence: 99%
“…The results were inconsistent with Hypericum hirsutum and Hypericum maculatum shoot cultures, in which jasmonic acid (JA) at higher concentration signi cantly inhibited biomass production and SA in uenced biomass production slightly in relation to control [34]. Recently, Jirakiattikul et al [35] also indicated JA to have minor effect on D. membranacea shoot cultures, whereas SA demonstrated no effect at all. In another study, it was found that MeJa reduced the growth of Centella asiatica culture at concentrations above 0.1 mM [36].…”
Section: Discussionmentioning
confidence: 97%
“…The production of psoralen was enhanced when MeJa and SA at 100 µM were added to the suspension culture of Psoralea corylifolia [42]. Therefore, MeJa has been well established as a key signal compound which was positively involved in the signal transduction pathway that leads to secondary metabolite production [43,35]. Diosgenin production was also favoured by SA which is a widely studied signaling molecule to trigger secondary metabolite production in plants [44].…”
Section: Discussionmentioning
confidence: 99%
“…The results were inconsistent with Hypericum hirsutum and Hypericum maculatum shoot cultures, in which jasmonic acid (JA) at higher concentration signi cantly inhibited biomass production and SA slightly effected biomass production relative to control [34]. Recently, Jirakiattikul et al [35] also indicated that, JA had low effect on D. membranacea shoot cultures, whereas SA had no effect. In an another study, it was found that MeJa reduced the Centella asiatica culture growth at concentration above 0.1 mM [36].…”
Section: Effect Of Elicitors On Shoot Biomass Accumulation Of Ddeltomentioning
confidence: 98%
“…The production of psoralen was enhanced when MeJa and SA at 100 µM was added to the suspension culture of Psoralea corylifolia [42]. Therefore, MeJa have been well established as key signal compounds and positively involved in the signal transduction pathway that leads to secondary metabolite production [43,35]. Diosgenin production was also favoured by SA which is widely studied signaling molecule to trigger secondary metabolite production in plants [44].…”
Section: Effect Of Elicitors On Diosgenin Production In Ddeltoidea Smentioning
confidence: 99%